Effects of delta-opioid receptor agonist pretreatment on the cardiotoxicity of bupivacaine in rats - Chenran Wang; Shen Sun; Jing Jiao; Xinhua Yu; Shaoqiang Huang (BMC Anesthesiology, 2022)
Abstract Background Delta-opioid receptor is widely expressed in human and rodent hearts, and has been proved to protect cardiomyocytes against ischemia/reperfusion and heart failure. The antagonist of delta-opioid receptor could block the rescue effect of lipid emulsion against local anesthetic cardiotoxicity. However, no evidence is available for the direct effect of delta-opioid-receptor agonists on the cardiotoxicity of local anesthetics. Methods Anesthetized Sprague Dawley rats were divided into five groups. Group NS received 2 ml·kg−1·min−1 normal saline, group LE received 2 ml·kg−1·min−1 30% lipid emulsion and group BW received 0.1, 1.0, or 5.0 mg/kg BW373U86, a delta-opioid-receptor agonist, for 5 min. Then 0.5% bupivacaine was infused intravenously at a rate of 3.0 mg·kg−1·min−1 until asystole. The time of arrhythmia, 50% mean arterial pressure-, 50% heart rate-reduction and asystole were recorded, and the dose of bupivacaine at each time point was calculated. Results All three different doses of BW373U86 did not affect the arrhythmia, 50% mean arterial pressure-reduction, 50% heart rate-reduction and asystole dose of bupivacaine compared with group NS. 30% LE significantly increased the bupivacaine threshold of 50% mean arterial pressure-reduction (17.9 [15.4–20.7] versus 7.2 [5.9–8.7], p = 0.018), 50% heart rate-reduction (18.7 ± 4.2 versus 8.8 ± 1.7, p < 0.001) and asystole (26.5 [21.0–29.1] versus 11.3 [10.7–13.4], p = 0.008) compared with group NS. There was no difference between group LE and group NS in the arrhythmia dose of bupivacaine (9.9 [8.9–11.7] versus 5.6 [4.5–7.0], p = 0.060). Conclusions Our data show that BW373U86 does not affect the cardiotoxicity of bupivacaine compared with NS control in rats. 30% LE pretreatment protects the myocardium against bupivacaine-induced cardiotoxicity.